IMPLEMENTATION OF ADVERTISING POSTER AS A PROMOTIONAL MEDIA FOR MSME - Ery Setiawan Nababan (Universitas Internasional Batam, 2022)
The purpose of this study was to determine how the effect of the application of advertising posters as a promotional medium for MSME (Micro, Small and Medium Enterprises). Utilization of advances in technology and information can be used by SME to promote their business. At this time the marketing process in the company that we are researching is still carried out by means of Word-of-mouth marketing (WOM), this process is a process of disseminating information that has been carried out for a long time but over time and the age of information has begun to spread using digital media therefore we want to implement social media marketing (SMM). The results of this study indicate that the application of advertising posters as a promotional medium for MSMEs has a positive effect on the development of MSME.